Novel COCH p.V123E Mutation, Causative of DFNA9 Sensorineural Hearing Loss and Vestibular Disorder, Shows Impaired Cochlin Post‐Translational Cleavage and Secretion. Issue 12 (27th August 2015) - Jung, Jinsei; Kim, Han Sang; Lee, Min Goo; Yang, Eun Jin; Choi, Jae Young
Abstract : Novel COCH p .V123E mutation causes progressive sensorineural hearing loss with autosomal dominant pattern. COCH mutations causing sensorineural hearing loss show impaired cochlin post‐translational cleavage and secretion. ABSTRACT: DFNA9 is an autosomal dominant disorder characterized by late‐onset, non‐syndromic hearing loss, and vestibular dysfunction. Mutations in the COCH (coagulation factor C homology) gene encoding cochlin are etiologically linked to DFNA9. Previous studies have shown that cochlin is cleaved by aggrecanase‐1 during inflammation in the spleen and that the cleaved LCCL domain functions as an innate immune mediator. However, the physiological role of cochlin in the inner ear is not completely understood. Here, we report that cochlins containing DFNA9‐linked mutations (p.P51S, p.V66G, p.G88E, p.I109T, p.W117R, p.V123E, and p.C162Y) demonstrate reduced cleavage by aggrecanase. Notably, in families affected with DFNA9, we found a novel COCH mutation causing p.V123E substitution in cochlin, which significantly reduced protein susceptibility to cleavage by aggrecanase (to about 20.5% of the wild‐type). These results suggest that the impaired post‐translational cleavage of cochlin mutants may be associated with pathological mechanisms underlying DFNA9‐related sensorineural hearing loss.